2000
DOI: 10.1046/j.1523-1755.2000.00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to both ICAM-1 and LFA-1 do not protect the kidney against toxic (HgCl2) injury

Abstract: Prevention of cellular infiltration by mAbs to LFA-1 and ICAM-1 has no effect on renal morphology, function, or regeneration following mercuric chloride-induced ARF in the rat. This result contrasts with the functional protection of the rat kidney to ischemia/reperfusion injury by virtue of an identical antibody treatment protocol. Resolving that controversy should bring better insight in fundamental processes underlying different types of ARF, and will be the subject of further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
(5 reference statements)
1
14
0
Order By: Relevance
“…Because it is often difficult clinically to differentiate ischemic from nephrotoxic ARF, it would be helpful to have agents that work in both ischemic and toxic injury. The anti-inflammatory agents ␣-melanocyte stimulating hormone (␣-MSH) and IL-10 and antibodies to intracellular adhesion molecule-1, lymphocyte function-associated antigen 1 (LFA-1), and TNF-␣ inhibit renal injury after ischemia but are ineffective as treatments for HgCl 2 -induced renal failure (9,10). This is possibly because the inflammatory phase of the nephrotoxic model occurs late, after the renal injury is established.…”
mentioning
confidence: 99%
“…Because it is often difficult clinically to differentiate ischemic from nephrotoxic ARF, it would be helpful to have agents that work in both ischemic and toxic injury. The anti-inflammatory agents ␣-melanocyte stimulating hormone (␣-MSH) and IL-10 and antibodies to intracellular adhesion molecule-1, lymphocyte function-associated antigen 1 (LFA-1), and TNF-␣ inhibit renal injury after ischemia but are ineffective as treatments for HgCl 2 -induced renal failure (9,10). This is possibly because the inflammatory phase of the nephrotoxic model occurs late, after the renal injury is established.…”
mentioning
confidence: 99%
“…Accordingly, Ang II-mediated tubular damage has been reported in diverse renal pathologies (Ruster and Wolf, 2006;Hayashi et al, 2010;Muñoz et al, 2011). According to previous reports using a similar HgCl 2 dose and timeline to induce nephropathy (Ghielli et al, 2000), normal values of serum creatinine were found in animals treated with HgCl 2 . During this experimental model, ARF is secondary to the back leak of tubular fluid due to the necrotic lesions induced by this toxin.…”
Section: Discussionmentioning
confidence: 62%
“…96 h) were based on the two following criteria: (1) it has been demonstrated previously that doses ranging from 1.0-3.5 mg HgCl 2 /kg induce dose-dependent alterations not only in the cytoplasm but also the nucleus of proximal tubule cells in the rat kidney (Stacchiotti et al, 2003); and (2) simultaneous ICAM-1 and ED-1 expression is related to the evolution time of HgCl 2 nephropathy (Ghielli et al, 2000;de Greef et al, 2003). Specifically, at 24 h post-HgCl 2 exposure, increased expression of ED-1 is not associated to ICAM-1 (de Greef et al 2003), but their co-expression is observed 2-6 days post-exposure (Ghielli et al 2000). Accordingly, since simultaneous expression of both molecules is associated with pro-inflammatory activity of Ang II, the experiments here were performed at day 4 (96 h) post-HgCl 2 injection.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Mercury is excreted almost exclusively via the kidney; thus, renal exposure to mercury is unavoidable and subsequent toxicity commonly evolves in the kidney (Madden & Fowler 2000). Renal mercury chloride (HgCl 2 )-induced damage has been studied using experimental models of nephropathy, showing that the toxic effects of HgCl 2 in the kidney are related to inflammatory events and/or oxidative stress (Ghielli et al 2000;Aleo et al 2002;Shimojo et al 2002;de Greef et al 2003;Stacchiotti et al 2003).…”
Section: Introductionmentioning
confidence: 99%